2000
DOI: 10.1177/1066480700084003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Family Cohesion, Adaptability, and Environment among Latino Families in Dissimilar Stages of Acculturation

Abstract: The present study examines the differences among Latino families who are in the low, bicultural, and high acculturation stages on measures of family cohesion, adaptability, and environment. Preliminary results revealed a significant difference in age of migration among the low acculturation and the bicultural and high acculturation groups. Therefore, a multiple analysis of covariance (MANCOVA) to control for age of migration was conducted. The results revealed significant differences among the groups on family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 33 publications
8
107
2
3
Order By: Relevance
“…Specifically, higher Mexican orientation was related to greater parenting efficacy and more parental involvement, which is consistent with past research demonstrating the "familism," or an emphasis on the closeness of the family, consistent discipline, and a strong family hierarchy, is a core Latino value (Miranda et al 2006;Miranda et al 2000;Rodriguez et al 2007). Additionally, initial evidence for the cultural validity of the CHOAS was supported by a trend suggesting that higher Anglo orientation was related to higher levels of family chaos, which may be explained by the acculturative stress that Latino families often face when adapting to a new culture (Finch and Vega 2003;Gil and Vega 1996;Miranda et al 2006;Miranda et al 2000;Sullivan et al 2007). …”
Section: Cultural Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…Specifically, higher Mexican orientation was related to greater parenting efficacy and more parental involvement, which is consistent with past research demonstrating the "familism," or an emphasis on the closeness of the family, consistent discipline, and a strong family hierarchy, is a core Latino value (Miranda et al 2006;Miranda et al 2000;Rodriguez et al 2007). Additionally, initial evidence for the cultural validity of the CHOAS was supported by a trend suggesting that higher Anglo orientation was related to higher levels of family chaos, which may be explained by the acculturative stress that Latino families often face when adapting to a new culture (Finch and Vega 2003;Gil and Vega 1996;Miranda et al 2006;Miranda et al 2000;Sullivan et al 2007). …”
Section: Cultural Propertiessupporting
confidence: 88%
“…The limited research available suggests that when Latino families (who traditionally display more collectivist and hierarchical family processes) come into contact with more individualistic and egalitarian cultures, the degree to which they adapt and acculturate greatly affects their parental/family functioning (for reviews see Bornstein and Cote 2006;Mio et al 2006). For example, parents who remain loyal to Latino values, such as "familism" and "respeto" tend to emphasize the closeness of the family, as well as structured rules and boundaries (Miranda et al 2006;Miranda et al 2000;Rodriguez et al 2007). These parents also keep discipline strategies consistent and often favor spanking and other forms of corporal punishment (see Halgunseth et al 2006 for a review; Monzo and Rueda 2006).…”
Section: Examination Of Cultural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has found that bicultural families report less conflict and higher adaptability. 35 Future research might benefit from including measures of bilingualism and biculturalism to enhance understanding of cultural maintenance and influence on health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…While the relationship between acculturation and family functioning is complex, there is some evidence that Latino families who are less acculturated report higher 50 levels of emotional and tangible support (Rodriguez et. al, 2007) and cohesiveness (Miranda, Estrada & Firpo-Jimenez, 2000). In addition, there is some evidence that the relationship between higher levels of acculturation in Latino adolescents and increased substance use can be explained by decreases in familism (Gil, Wagner & Vega, 2000).…”
Section: African Americansmentioning
confidence: 99%